2016
DOI: 10.1111/pme.12899
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the Percutaneous Absorption of Ketamine HCl, Gabapentin, Clonidine HCl, and Baclofen, in Compounded Transdermal Pain Formulations, Using the Franz Finite Dose Model

Abstract: This study suggests that the combination of these 4 analgesic drugs can be successfully delivered transdermally, using either Lipoderm or Lipoderm ActiveMax. Compounded transdermal drug preparations may then provide physicians with an alternative to traditional oral pain management regimens that can be personalized to the specific patient with the potential for enhanced pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Choices include three of the most commonly used topical analgesics for chronic neuropathic pain: ketamine, clonidine, and gabapentin, with ketamine having the highest absorption rate. 15 Clonidine has been used as an adjuvant pain medication successfully in postoperative and chronic pain. As a relatively nonspecific a 2 -agonist, it acts to hyperpolarize nerve cell membranes, diminishing nociceptive function, and lowering circulating levels of catecholamines.…”
Section: Discussion: the Need To Recognize Topical Adjuvant Analgesicmentioning
confidence: 99%
See 2 more Smart Citations
“…Choices include three of the most commonly used topical analgesics for chronic neuropathic pain: ketamine, clonidine, and gabapentin, with ketamine having the highest absorption rate. 15 Clonidine has been used as an adjuvant pain medication successfully in postoperative and chronic pain. As a relatively nonspecific a 2 -agonist, it acts to hyperpolarize nerve cell membranes, diminishing nociceptive function, and lowering circulating levels of catecholamines.…”
Section: Discussion: the Need To Recognize Topical Adjuvant Analgesicmentioning
confidence: 99%
“…Choices include three of the most commonly used topical analgesics for chronic neuropathic pain: ketamine, clonidine, and gabapentin, with ketamine having the highest absorption rate. 15 …”
Section: Discussion: the Need To Recognize Topical Adjuvant Analgesicmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vitro study of human cadaver trunk skin revealed that clonidine can be successfully delivered transdermally for analgesic effects when incorporated into transdermal lipoderm compound bases. Furthermore, clonidine, approximately 1 hr after application on trunk skin, had a rapid penetration to peak flux and a secondary peak at approximately 40 hr (Bassani & Banov, ). Although the systemic delivery of clonidine has attenuated hyperalgesia in several pain models, the clinical use of clonidine is dose limited, because of its adverse side effects such as drowsiness, hypotension, and sedation.…”
Section: α2‐adrenoceptors As a Target For Neuropathic Pain Treatment;mentioning
confidence: 99%
“…Ketamine is usually combined with gabapentin, clonidine and baclofen, using either transdermal Lipoderm or Lipoderm ActiveMax. This technique can personalize treatment thus embettering focal pain control [233]. Also, topical ketamine cream, compounded in combination with other drugs (amitriptyline, baclofen, lidocaine, ketoprofen, clonidine, gabapentin, pregabalin), was reported by this group with excellent pain control in patients suffering from peripheral neuropathic pain [55].…”
Section: Topical (External) Use Of Ketaminementioning
confidence: 99%